Commercial, Cooking and Eating Quality Traits and Nutrient Values of Local Mixed Black and White Rice from Yogyakarta - Mary Astuti; Sri Kanoni; Mega Mustika; Oki Krisbianto (Indonesian Association of Food Technologists, 2017)
Black rice has higher anthocyanin content and other nutritional values than white rice but is not preferable as staple food by Indonesian people especially for its aroma and texture. Mixing black rice with white rice was expected to increased its cooking and eating qualities but might be affected its commercial and nutritional qualities. Local cultivars of black rice Cempo Ireng and white rice Mentik Wangi were mixed at ratios 1:0 (S1), 3:1 (S2), 1:1 (S3), 1:3 (S4) and 0:1 (S5) w/w. The raw and cooked mixed rice were physically, chemically, physicochemically and sensorily analyzed to determined its commercial, cooking, eating and nutritional qualities. The addition of white rice increased the cooking and eating qualities of mixed rice but reduce its nutritional value. It had been suggested that the ratio of black rice and white rice must not lower than 1:1 to preserve its eating and nutritional qualities.